Properties of Metal Oxide and Pineapple Fiber Reinforced Dental Composite Resin - Asri, R.I.S.; Sunendar, B.; Dwiandhono, I.; Harmaji, A. (Physics and Chemistry of Solid State, 2023)
This study aimed to synthesize fillers in the form of alumina-zirconia-carbonate apatite and pineapple leaf fiber (Ananas comosus (L.) Merr) as matrix reinforcement consisting of UDMA, TEGDMA, and DMAEMA for direct dental restoration applications. The sample consisted of four composite groups with the addition of 0-5% fiber. All composite samples were then tested for hardness, flexural strength, and Scanning Electron Microscope (SEM). The results of the composite hardness test without the addition of fiber were 30.31 VHN. With the addition of 1%, 2.5%, and 5% fiber, the composite has a hardness value of 31.13 VHN, 34.02 VHN, and 27.22 VHN, respectively. The results of the three-point bending test showed that the flexural strength of the sample without the addition of fiber was 1.6 MPa, while the addition of 1%, 2.5%, and 5% fiber resulted in the flexural strength of 2.1 MPa, 2.3 MPa, and 1.8 MPa, respectively. The SEM results show a homogeneous particle dispersion morphology, with various agglomerations and gaps. Composites with the addition of 1% and 2.5% fiber have a narrower gap than without the addition of fiber. This explains the increase in the hardness and flexural strength of the composite.